Pengaruh Aktivitas Fisik Teratur terhadap Sistem Imun dan Kesehatan Mental: Literature Review - Afrizal Bagaskara; Ni Made Laksmi Devi Jayanti; I Komang Aditya Negara (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Regular physical activity is known to play an important role in maintaining overall health, including improving immune system function and mental health. Lack of physical activity remains a public health issue, making it important to understand the impact of physical activity on the immune system and mental health. This study aimed to review the effect of regular physical activity on the immune system and mental health using a literature review method. The literature sources were obtained from publications within the last five years using databases such as Google Scholar, PubMed, and ScienceDirect. The articles were then screened and selected based on inclusion and exclusion criteria, resulting in nine relevant articles for analysis. The selection results indicate that regular physical activity can increase the mobilization and activity of immune cells such as lymphocytes, neutrophils, and natural killer cells, and also modify the adaptive immune system through changes in T cells and B cells. In addition, physical activity also improves mental health through neurobiological mechanisms such as increased endorphin, dopamine, and serotonin levels, which can reduce stress, anxiety, and depression, as well as improve sleep quality and psychological well-being. Therefore, regular physical activity has a positive effect on the immune system and mental health and can be used as a promotive and preventive strategy to maintain overall health.